Aktivitas Masyarakat Terhadap Pemanfaatan Lahan dalam Memenuhi Kebutuhan Hidup di Kecamatan Singkawang Selatan: COMMUNITY ACTIVITIES ON LAND UTILIZATION IN FULFILLING LIVING NEEDS IN SINGKAWANG SELATAN DISTRICT - Zhumuarin Brilliandi, Firdan; Trismi Harjanti, Diah; Ulfah, Maria; Anasi, Putri Tipa (Innovative: Journal Of Social Science Research, 2025)
This research aims to examine how people in the South Singkawang District carry out land management and utilization activities, arid land and wetlands in the District, in an effort to maintain their household food security. The data collection technique in this research uses triangulation techniques, namely a combination of observation techniques, interview techniques and documentation techniques. Data analysis uses data reduction models, data presentation and drawing conclusions. This research investigates agricultural activities and food security in South Singkawang District. The results of observations and interviews show differences in the use of dry and wet land. On dry land, crops such as taro, corn and fruit are grown with the majority of the harvest being sold directly, except taro which is processed into chips. In wetlands, the majority are planted with various types of rice for different purposes, such as seed raising or sale. Although the majority of respondents rely on agriculture to meet their living needs, only a small percentage are successful in doing so. Factors such as traditional land cultivation and land size influence the achievement of farmers' subsistence needs. Keywords: Utilization Activity, Land Management, Living Needs